Information and Communication Technologies Use in the Process of Teaching Higher Mathematics at the Technical Universities of Ukraine - Rashevs’ka, Nataliya; Kiyanovs’ka, Nataliya (Pedagogical Discourse, 2013)
The article analyzes the ICT of teaching higher mathematics, which are used in the training of students in the higher technical educational institutions of Ukraine. Among them it studies software and educational tools, software protection, electronic teaching aids, developers of which are domestic scholars. The features of these technologies, their potential and purpose, selected teaching goals using information and communication technology in learning higher mathematics are examined. Classification of software and teaching tools for architecture levels, the way they represent branches of mathematics and the degree of autonomy are classified; didactic conditions of developing of software and teaching tools are given.